The application of the "Make a Match" model to improve Indonesian language learning outcomes for elementary school students - Maiyolanda, Agnita; Pebriana, Putri Hana; Rahmatullah, Emeliani; Hasfarina, Fitri; Cahyati, Ledy; Umairah, Nur; Rahmadiah, Putri; Rahmayani, Rini; Saffiyah, Wardina (The Future of Education Journal, 2025)
This research aims to analyze the application of the Make a Match learning model to improve elementary school students' Indonesian language learning outcomes through the literature analysis method. Make a Match is a cooperative learning model that involves matching cards with questions and answers, thereby creating an active, fun and interactive learning atmosphere. In this research, various relevant journal articles, books and research were analyzed to evaluate the effectiveness of the model. The results of the literature review show that Make a Match can improve student learning outcomes by motivating active participation, improving memory and increasing understanding of lesson material. Apart from that, this model is able to improve the atmosphere in the classroom and improve students' social skills. Based on these results, Make a Match is suggested as an effective strategy to be implemented in teaching Indonesian at the elementary school level.